A legítima defesa como pressuposto de uso da força e da guerra no direito internacional - Carvalho, Emanoel José de (2013)
This monograph examines the factual aspects, theoretical and legal treatment given to the use of force and war as a means of resolving conflicts and disagreements in the international sphere. Seeks to analyze the concept of just war as a way of legitimizing the war. Legitimate defense is studied as well as the foundation of war and use of force, in its various possibilities, especially in the face of a world in which many forms of wars then legally proscribed. It is as if the current legal treatment given to the war, with a preponderance of the provisions of the UN Charter, in Chapter VII, in particular Article 51 which provides for the possibility of selfdefense for its members. Analyzes, the end, the most controversial form of self-defense, self defense preventive, with emphasis on their specific cases, narrating the historical incidents in which the argument was used often in total disregard to historical truth. Historical and doctrinal aspects are used throughout the study as a way to support the conclusions obtained at the end of the work.